Fast DNA Vaccination Strategy Elicits a Stronger Immune Response Dependent on CD8+CD11c+ Cell Accumulation - Liu, Chenlu; Cong, Xianling; Wang, Yuqian; Guo, Qianqian; Xie, Yu; Geng, Fei; Guo, Jie; Dong, Ling; Zhou, Yi; Wu, Hui; Yu, Bin; Wu, Jiaxin; et al. (Frontiers in Oncology, 2021)
Conventional DNA vaccine strategies usually employ a regimen of immunizations at two-week or longer intervals to induce effective memory cell-dependent immune responses. Clinical cancer treatment requires a faster immunization strategy to contend with tumor progression. In this study, a novel fast immunization strategy was established, wherein a DNA vaccine was intramuscularly administered on days 0, 2, and 5 in a murine lung cancer model. Effector cells peaked seven to ten days after the last vaccination. Compared with traditional two-week-interval immunization strategies, antigen-specific cytolysis and INF-γ secretion were significantly enhanced under the fast vaccination approach. As a result, the rapidly administered DNA vaccine elicited stronger and more prompt anti-tumor effects. The probable underlying mechanism of fast immunization was the accumulation of CD8+CD11c+ antigen-presenting cells at the injection site, which enhanced subsequent antigen presentation. In conclusion, the fast DNA vaccination strategy shortened vaccination time to five days and elicited a stronger anti-tumor immune response.